Factors Influencing Purchase Intention - Muslimah, Ine; Satria, Fajar (Yayasan Gema Bina Nusantara, 2026)
Cosmetic industry is one of sector that has billion dollar value in the world, the product suce as : facial cleanser, toner, serum, moisturizer, foundation, lipstick, eyeliner, eyeshadow, blush on, and mascara. In this research purpose is to know and to analyze the effect that brand image, brand awareness, brand loyalty, perceived quality and E-WOM produce for purchase intention. The analysis metode in this research is multiple linier regresion. The population in this research is all of respondens who used skincare that come from korea and it contain exfoliation serum, therefore the researcher is the population who used exfoliation serum from Jakarta namely Elformula. There are 120 responden who used non-probability sampling metode. The reseacher's ways to collect the data is using google from and that will be shared. The result of the image variable brand, awareness breand, loyaly brand, quality perceived and E-WOM is it has big positive effect that can make purchase intention. This research will help the marketing and people has a knowledge to choose a segmentation, pisitioning, and market targeting. And this research bas some managerial implications for companies and skincare seller namely Elformula.